Block of nicotinic acetylcholine receptors by philanthotoxins is strongly dependent on their subunit composition - Kachel, Hamid S.; Patel, Rohit N.; Franzyk, Henrik; Mellor, Ian R. (Nature Publishing Group, 2016)
Philanthotoxin-433 (PhTX-433) is an active component of the venom from the Egyptian digger wasp, Philanthus triangulum. PhTX-433 inhibits several excitatory ligand-gated ion channels, and to improve selectivity two synthetic analogues, PhTX-343 and PhTX-12, were developed. Previous work showed a 22-fold selectivity of PhTX-12 over PhTX-343 for embryonic muscle-type nicotinic acetylcholine receptors (nAChRs) in TE671 cells. We investigated their inhibition of different neuronal nAChR subunit combinations as well as of embryonic muscle receptors expressed in Xenopus oocytes. Whole-cell currents in response to application of acetylcholine alone or co-applied with PhTX analogue were studied by using two-electrode voltage-clamp. α3β4 nAChRs were most sensitive to PhTX-343 (IC50=12 nM at −80 mV) with α4β4, α4β2, α3β2, α7 and α1β1γδ being 5, 26, 114, 422 and 992 times less sensitive. In contrast α1β1γδ was most sensitive to PhTX-12 along with α3β4 (IC50values of 100 nM) with α4β4, α4β2, α3β2 and α7 being 3, 3, 26 and 49 times less sensitive. PhTX-343 inhibition was strongly voltage-dependent for all subunit combinations except α7, whereas this was not the case for PhTX-12 for which weak voltage dependence was observed. We conclude that PhTX-343 mainly acts as an open-channel blocker of nAChRs with strong subtype selectivity.